A case study of dynamic behaviour of short span concrete slab bridge reinforced by tire-derived aggregates as sub-ballast. Issue 1 (2nd January 2020) - Esmaeili, Morteza; Ataei, Shervan; Siahkouhi, Mohammad
ABSTRACT: In the current study, the dynamic behaviour of a 6-m short span railway bridge with the concrete deck was investigated with and without 200 mm thickness tire-derived aggregate (TDA) layer as a shock absorber. The dynamic performance of the bridge was assessed under GT26 diesel loads for two moving speeds of 20 and 50 km/h in the field. The results showed an increase in track–bridge natural frequency from 20 to 23 Hz due to TDA layer installation. Moreover, maximum acceleration of sleeper and the maximum acceleration along with longitudinal strain of the bridge deck have been decreased by 71%, 40%, and 58%, respectively, for the speed of 20 km/h versus to 63%, 33%, and 58% at the speed of 50 km/h.